Bori - Pinus spp. - Jurc, Dušan (Gozdarski vestnik, 2007)
The most frequent diseases of oaks leaves in Slovenia are presented. Most important is oak mildew (Microsphaera alphitoides), which affects above all pedunculate oak and sessile oak. Accurately are presented anamorph and teleomorph, symtoms of the disease and ecological factors which influence the disease development. Possibilities of chemical control of the disease are described and the most recent findings in connection with biological control, which is based upon use of the fungus Ampelomyces quisqualis. Described are also diseases caused by two endophytic fungi Discula quercina and Tubakia dryina, which occurr commonly throughout Slovenia but they do not affect oaks seriously.
Keywords: bori; Pinus spp.; poganjki; bolezni; disease; debla; zdravje gozdov